031 Use of the novel sideguard dedicated bifurcation stent: a real world experience. (16th May 2012) - Sastry, S; Mamas, M; Palmer, K; Iles-Smith, H; El-Omar, M; Fraser, D; Fath-Ordoubadi, F
Abstract : Introduction: PCI treatment of bifurcation disease is technically challenging. Dedicated bifurcation stents have been developed to address some of the challenges associated with bifurcation lesions. The aim of this study is to report clinical utility and outcomes of the Sideguard stent in patients undergoing treatment to bifurcation coronary lesions in a real world setting in a large tertiary UK centre. Methods: Retrospective study of 61 consecutive patients treated with the Sideguard Stent for bifurcation PCI at the Manchester Heart Centre from March 2010 to October 2011. Patient demographics and PCI procedural data were obtained from the in-house, cross validated PCI database. Mortality data were obtained from National Office of Statistics. Interim 6 month and 1 year data were obtained from clinical review. Clinical end point studied included death, subsequent myocardial infarction, stent thrombosis and target lesion/vessel revascularisation (TLR/TVR). Results: A total of 61 consecutive patients underwent bifurcation PCI using the Sideguard stent during this study. Mean age 57.1±11.5 years (range 30–76) of which 50/61 were male (81.9%). Bifurcation site was in LAD in 44 (72.2%), Cx in 14 (22.9%) and RCA in 3 (4.9%) of cases. Medina classification was 1:1:1 in 38 (62.3%), 1:0:1 in 10 (16.3%) and 0:1:1 in 6 (9.9%) of cases. Moderate or severe calcification was present in 27 (44.3%) of cases. Mean main vessel (MV) diameter was 3.36±0.39 mm, mean MV stent length was 35±18.4 mm and mean number of stents in MV was 1.54±0.77. Mean Side branch vessel (SB) diameter was 2.93±0.33 mm, mean SB stent length was 13.4±8.5 mm and mean number of stents in SB was 1.24±0.43. Final kissing balloon was attempted in 57 (93.4%) and successful in all cases attempted. Procedural complications occurred in 4/61 (6.6%) cases. Complications included 1 case of limited perforation of the MB which was treated conservatively, 1 case of clot formation related to IVUS examination (neither of these complications were thought to be related to sidegurad stent, directly) and 2 cases of stent displacement. Local deployment techniques have been modified to combat displacement. Operators now wait for 30 s and take a frame shot after stent deployment to confirm placement before removing the stent balloon. In our interim analysis 43 of these 61 patients have been followed up for at least 6 months (70.5%) and 37 patients for at least 1 year (60.7%). There were no deaths or stent thromboses. There was no TLR at 6 month and only 2 (3.3%) at 1 year. TVR was 1 (1.6%) at 6 month with no further cases at 1 year. Conclusions: In one of the largest clinical experiences to date, the Sideguard stent can be used to treat complex bifurcation lesions in a straight forward manner, with excellent short and long term clinical outcomes.